2003
DOI: 10.1017/s0142716403000134
|View full text |Cite
|
Sign up to set email alerts
|

Nonword reading across orthographies: How flexible is the choice of reading units?

Abstract: International audienceIt was predicted that children learning to read inconsistent orthographies (e.g., English) should show considerable flexibility in making use of spelling-sound correspondences at different unit sizes whereas children learning to read consistent orthographies (e.g., German) should mainly employ small-size grapheme-phoneme strategies. This hypothesis was tested in a cross-language blocking experiment using nonwords that could only be read using small-site grapheme-phoneme correspondences (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
0
21

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 22 publications
6
109
0
21
Order By: Relevance
“…Depending on what language they speak and how well they read, children seem to move rapidly from reliance on surface units (letters) to reliance on more abstract units (graphemes) and larger sublexical units such as onsetrhymes and/or syllables. In English, it is probably because taking word rhymes into account reduces the inconsistencies of GPCs that beginning English readers make greater use of rhyme units (Brown & Deavers, 1999;Goswami et al, 1998;Goswami, Ziegler, Dalton, & Schneider, 2003), unlike beginners in languages with a shallower orthography who mostly rely on GPCs. This is true of Spanish and French (Goswami et al, 1998;Sprenger-Charolles et al, 1998), and even German (Goswami et al, 2003), despite the fact that in German, as in English, there are a greater number of closed than open syllables and thus more opportunity to process rhyme units.…”
Section: Main Variables In the Study Of Literacy Acquisition: A Shortmentioning
confidence: 99%
“…Depending on what language they speak and how well they read, children seem to move rapidly from reliance on surface units (letters) to reliance on more abstract units (graphemes) and larger sublexical units such as onsetrhymes and/or syllables. In English, it is probably because taking word rhymes into account reduces the inconsistencies of GPCs that beginning English readers make greater use of rhyme units (Brown & Deavers, 1999;Goswami et al, 1998;Goswami, Ziegler, Dalton, & Schneider, 2003), unlike beginners in languages with a shallower orthography who mostly rely on GPCs. This is true of Spanish and French (Goswami et al, 1998;Sprenger-Charolles et al, 1998), and even German (Goswami et al, 2003), despite the fact that in German, as in English, there are a greater number of closed than open syllables and thus more opportunity to process rhyme units.…”
Section: Main Variables In the Study Of Literacy Acquisition: A Shortmentioning
confidence: 99%
“…According to this view, both unit types are potentially available for use fairly early in the development of reading (Stuart, Masterson, Dixon, & Quinlan, 1999) as learners develop a sight vocabulary. Most modern models of word reading in adults suggest that the lexicon contains information that pertains to both rime and GPC units (e.g., Brown, 1998), some of which seems to be driven by the characteristics of English spelling-sound mappings (Goswami, Ziegler, Dalton, & Schneider, 2003). According to this model, words units are applied flexibly and differentially according to the demand characteristics of the task.…”
Section: Discussionmentioning
confidence: 99%
“…Brown and Deavers (1999) for instance, noted that adults shifted the pronunciation of ambiguous nonwords towards rime pronunciations when the list contained a high proportion of rime-based items on it. Similarly, Goswami, Ziegler, Dalton, and Schneider (2003) compared the reading of three kinds of nonword lists: small-unit nonwords (regular GPC pronunciations), large-unit nonwords (rime pronunciations), and a mixed list that combined both types of words. They found that English adults performed more accurately and quickly on small-unit lists and large-unit lists than on the mixed list, showing what the authors called a "switching cost".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to reading performance, the most economic strategy with the lowest memory effort would therefore be to link graphemes to phonemes, because for reading acquisition it is necessary to assign a phonological representation to a printed word. In the German language this is a suitable reading strategy, since graphemes usually map to only one phoneme 1 (Goswami, Ziegler, Dalton, & Schneider, 2003;Jacobs, 2002;Jacobs & Graf, 2005;Ziegler, Perry, Jacobs, & Braun, 2001). However, in languages with more inconsistent graphemeto-phoneme correspondences (GPC) larger units may be more suitable for reading acquisition.…”
mentioning
confidence: 99%